Could the deep squat jump predict weightlifting performance? - Vizcaya, F. J.; Viana, O.; del Olmo, M. F.; Acero, R. M. (The Journal of Strength and Conditioning Research, 2009)
This research was carried out with the aim of describing the deep squat jump (DSJ) and comparing it with the squat (SJ) and countermovement (CMJ) jumps, to introduce it as a strength testing tool in the monitoring and control of training in strength and power sports. Forty-eight male subjects (21 weightlifters, 12 triathletes, and 15 physical education students) performed 3 trials of DSJ, SJ, and CMJ with a 1-minute rest among them. For the weightlifters, snatch and clean and jerk results during the Spanish Championship 2004 and the 35th EU Championships 2007 were collected to study the relationship among vertical jumps and weightlifters' performance. A 1-way analysis of variance (ANOVA) showed significant differences between groups in the vertical jumps, with the highest jumps for the weightlifters and the lowest for the triathletes. An ANOVA for repeated measures (type of jump) showed better results for DSJ and CMJ than SJ in all groups. A linear regression analysis was performed to determine the association between weightlifting and vertical jump performances. Correlations among the weightlifting performance and the vertical jumps were also calculated and determined using Pearson r. Results have shown that both CMJ and DSJ are strongly correlated with weightlifting ability. Therefore, both measures can be useful for coaches as a strength testing tool in the monitoring and control of training in weightlifting.